Preliminary Review of the Effects of Electronic Medical Administration Records (eMAR) and Electronic Doctor Order Entry (CPOE) on Patient Safety Culture in the Era of Universal Health Services - Rahmat Santoso; Stefanus Nova (Universitas Katolik Soegijapranata Semarang, 2019)
In the era of universal health service [UHC], medicine was always used as part of curative, preventive, and promotive. Following pharmaceutical service standards in hospitals, health centers, and pharmacies, that medicines must be managed properly, including in their use. Medication errors are a leading cause of death in many parts of the world. The factors causing the increase in medication errors related to individuals, such as heavy workload on health care facilities and pharmaceutical service facilities, are often experienced by medical staff (General Practitioners and Specialists) and pharmaceutical personnel (Pharmacists and Pharmaceutical Technical Personnel / TTK), or organizational-related factors, such as inadequate facilities and infrastructure to document medication administration records and the entry of physician orders electronically. The study was conducted cross-sectionally retrospectively, by sharing the results of an initial literature review on the impact of electronic medication administration records (eMAR) and doctor's order entry (CPOE) on patient safety. Using PubMed and Google Scholar, we search for the following terms: